Driving University Performance in the Artificial Intelligence Era: Digital Skills, Creative Leadership, and Innovation under Vision 2030 - Shah , Syed Afzal Moshadi; Khan , Aqil Waqar; Fatima, Noureen; Seraj, Abdullah Hamoud Ali; Ozturk, Ilknur; Zaman, Khalid (International Review of Management and Marketing, 2026)
Universities in the digital era seek new methods to enhance faculty productivity, fulfill national strategic objectives, and stay competitive globally. This study examines how digital competency, organizational support for innovation, entrepreneurial mindset, organizational adoption of AI, and job performance affect Saudi academic and administrative staff in light of Vision 2030. Employee creativity and transformative leadership moderate the performance connection. The stratified random sample poll included 775 respondents from nine Saudi universities. The structural equation modeling with high fit indices validates the measurement model’s validity and reliability. Digital proficiency, innovation support, job performance, and AI usage are positively connected with an entrepreneurial attitude. Digital proficiency, corporate support for innovation, entrepreneurial mentality, and AI usage all affect employee creativity and initiative. Moderate analysis shows that transformative leadership boosts corporate productivity and creativity. Creative performance is higher under powerful transformational leadership conditions than without leadership, as shown by the interaction effect. The bootstrapped resamples-based mediation approach links employee creativity to task performance. Creativity bridges organizational and technological behaviors, improving performance. Strategic higher education policy affects Vision 2030’s innovation, global competitiveness, and institutional excellence goals.